Evaluation of Antioxidant and Anti Parkinsonism Activity of Betaine in Experimental Rats - Masule, Milind V.; Shinde, Sachin D.; Kurkute, Sujata S.; Salve, Balu (Journal of Drug Delivery and Therapeutics, 2019)
Aim and Objectives: The present study was aimed to evaluate anti parkinsonium effect of Betaine for its Applications in trigger factors in pathogenesis of Parkinson’s disease and to understand development of new treatments approaches for PD. Betaine is naturally obtained product. It has antioxidant, neuroprotective activity. Hence, we inspected whether betaine can act as a protective agent in 6-OHDA induced oxidative stress on cerebellum of Sprague-Dawleyrats.Material and Methods Thirty-six adult Sprague-Dawley rats were dived into six groups. Rats were received unilateral 6- hydroxydopamine lesions for induction except normal and rats were treated with respective treatment. At the day of 21 rats were sacrificed. Prepared brain homogenate was used for further Biochemical estimation.Result: Betaine showed marked rise in SOD and Catalase activity as well as GSH content subsequently decreasing in the lipid peroxidation process. Our result suggests Betaine to be potent antioxidant at dose 12.5 and 25 mg/kg as compared to standard (L-dopa+Benserazide) and pro-inflammatory cytokines viz: TNF-α, IL-1β and IL-6 were significantly reversed by Betaine as compared to that of standard group (L-dopa+ Benserazide).Discussion and Conclusion: Betaine showed dose dependent effect by reducing LPO level as increasing SOD, GSH and Catalase activity and marked reduced proinflammatory cytokine, hence we conclude that betaine has good anti parkinsonism activity.Keywords: 6-OHDA, Antioxidant, Betaine, Pro-inflammatory cytokines.